Market distortions and government transparency - Albornoz, Facundo; Esteban, Joan; Vanin, Paolo (Wiley, 2014)
In this paper, we investigate how government transparency depends on economic distortions. We first consider an abstract class of economies in which a benevolent policy maker is privately informed about the exogenous state of the economy and contemplates whether to release this information. Our key result is that distortions limit communication: even if transparency is ex ante Pareto superior to opaqueness, it cannot constitute an equilibrium when distortions are sufficiently high. We next confirm this broad insight in two applied contexts, in which monopoly power and income taxes are the specific sources of distortions. (JEL: D82, E61)